RANCANGAN PERSEDIAAN BAHAN BAKU DENGAN MENGGUNAKAN METODE EOQ STUDI KASUS PADA PERUSAHAAN ROKOK KETAPANG JAYA TANGGULANGIN SIDOARJO - Imelda, Patricia; Irwandi, Soni Agus (Universitas Hayam Wuruk Perbanas, 2011)
In the procurement of raw material inventory, the company can not be separated from the design, control, and processing of raw materials that cover many functions: purchasing function, irregularities or warehousing, production and accounting administration. EOQ method can be applied in the company of Ketapang Jaya to manage the inventory of raw materials. Besides that, it also enables them control their inventory in the optimum volume and efficiency. Therefore, this paper tries to find out the way of how companies implement the draft inventory of raw materials when using the EOQ method to improve cost efficiency. It is also expected to be able to measure and find out the inventory of raw materials by using the EOQ method as a means to improve the cost efficiency of raw materials at Tobacco Company of Ketapang Jaya. The methodology used in this research is interviews, observation, and documents (secondary data). Beside, it also conducts a descriptive analysis both qualitatively and quantitatively by comparing the EOQ method and traditional methods. It can be conducted that using the EOQ method, it can increase the productivity optimally and efficiently for the use of raw materials.